Using video-analysis in the professional development of a classroom teacher. Issue 2 (1st February 2021) - Heard, Kim; Peltier, Corey
Abstract: Professional development for educators is often not evidence-based and insufficient to improve classroom management skills. Video-analysis has been shown to be effective at improving pedagogy of classroom teachers. We expanded on prior literature by using an early childhood general education teacher. A multiple baseline design across behaviors was used to evaluate the efficacy of a training model on providing opportunities to respond (OTR) and behavior-specific praise (BSP), and how this may reduce the need for corrective statements. Frequency data was obtained via 15 min video sessions. Results indicate that the intervention was functionally related to the two dependent variables. Effects were stronger for increasing the teacher's usage of OTR and BSP than in the reduction of corrective statements.